(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article is devoted to the theoretical substantiation of the need for scientific research of the personality of a criminal who involves minors in illegal activities, drunkenness, begging, gambling. Attention is focused on the fact that the criminological study of persons engaged in the involvement of minors in illegal activities is not only of legal interest, but also of social interest, because it touches deeply moral, or rather immoral aspects of the behavior of adults who involve minors in illegal activities. It has been determined that this is a crime. It is concluded that the key role of the criminal's personality in the commission of involving minors in illegal activities is carried out, because it is he